Assessment of Pre-extubating Recurrent Laryngeal Nerve Palsy using Ultrasound in Postoperative Patients with Esophageal Cancer: A Retrospective Study - Khan, Laila; Umar Shahid, Hafiz Muhammad; Kumar, Pavan; Ramachandran, Vignesh; Butt, Esha Habib; Kalim, Muhammad (Journal of Neonatal Surgery, 2025)
Background: To evaluate the feasibility and diagnostic accuracy of pre-extubation RLN assessment using bedside ultrasound in patients undergoing esophagectomy for esophageal cancer. Methods: This retrospective study included 72 patients who underwent elective transhiatal or transthoracic esophagectomy from March 2023 and March 2024. Demographic, surgical, and anesthetic data collected. RLN function was assessed pre-extubation using high-frequency laryngeal ultrasound and findings compared with postoperative laryngoscopic confirmation and clinical outcomes. Statistical analysis was performed using Chi-square and Fisher’s exact tests, with p < 0.05 considered significant. Results: Ultrasound visualization of RLN mobility was successful in 94.4% of patients. RLN palsy was detected in 16.7%, with a strong correlation with laryngoscopic confirmation (p = 0.002). Patients with abnormal ultrasound findings had significantly higher rates of hoarseness (p = 0.005), stridor/re-intubation (p = 0.017), and prolonged ICU stay (p = 0.026). Conclusion: Pre-extubation ultrasound is a feasible and reliable tool for early detection of RLN palsy after esophagectomy. Its routine use may improve patient safety by identifying those at risk for airway complications before extubation